Designing of an innovative conserved multiepitope subunit vaccine targeting SARS-CoV-2 glycoprotein and nucleoprotein through immunoinformatic - Temitope Isaac Adelusi; Abdeen Tunde Ogunlana; Moyosoluwa Precious Oyewole; Taiwo Ooreoluwa Ojo; Olamide Tosin Olaoba; Elijah Kolawole Oladipo; Shopnil Akash; Samir Ibenmoussa; Mohammed Bourhia; Yousef A. Bin Jardan; Baye Sitotaw (Scientific Reports)
Abstract The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has imposed substantial challenges on our society due to the COVID-19 pandemic. This virus relies heavily on its surface glycoprotein (S-glycoprotein) to facilitate attachment, fusion, and entry into host cells. While the nucleoprotein (N) in the ribonucleoprotein core binds to the viral RNA genome. Therefore, our objective is to develop a novel vaccine candidate targeting the dominant T-cell and B-cell epitopes of the immune system. On the S-glycoprotein and nucleoprotein. Employing an immunoinformatic approach, we constructed a vaccine candidate with 13 highly antigenic B-cell epitopes, 19 HTL antigenic epitopes, and 18 CTL epitopes following a rigorous assessment. The multi-epitope construct successfully passed three-fold toxicity, allergenicity, and antigenicity tests, affirming its non-toxic, non-allergenic, and antigenic nature. This demonstrates the potentiality of the vaccine design to trigger an immunological response. Furthermore, the vaccine-ACE-2 receptor complex was tested, confirming its ability to interact with ACE-2’s core pocket and induce an immunological response. Additionally, the vaccine’s binding prowess for human toll-like receptors (TLR) (1, 3, 4, and 8) was investigated. According to the Ramachandran plot, 77.46% of the construct’s amino acid residues fall within a favorable zone, establishing it as a viable vaccine candidate.